Development of PHYVAR (Physics in 3d Virtual Reality) on Solar Energy Material to Support Students’ Spatial Intelligence - Fauziah, Siti Sepiyanti; Guntara, Yudi; Septiyanto, Rahmat Firman (Department of Physics Education, Universitas Mataram, 2024)
Spatial intelligence, as proposed by Howard Gardner's theory of multiple intelligences, is one of eight different intelligences that every individual has. The 9 intelligences include: visual-spatial intelligence, linguistic-verbal intelligence, logical-mathematical intelligence, physical-kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalistic intelligence and existential intelligence. Spatial intelligence includes a person's ability to visualize objects complexly in three dimensions, manipulate an object to make it appear realistic and understand spatial relationships with physical phenomena. This form of intelligence plays an important role in various fields, including but not limited to physics, engineering, architecture, and scientific exploration. In this field, the capacity to conceptualize and work with spatial elements is fundamental to problem solving and innovation. Solar energy, also known as solar power or solar radiation, is a renewable and sustainable energy source that comes from the sun. Its significance is critical in overcoming global challenges related to energy security, climate change mitigation and environmental sustainability. The integration of solar energy topics into the class is critical. In particular, point 7 of the goal emphasizes the ambition to achieve universal access to affordable, reliable, sustainable and modern energy services by 2030, making solar energy education an integral part of preparing students for a sustainable future. The main objective of the research discussed is to test the feasibility of PHYVAR (Physics in 3D Virtual Reality) on Solar Energy material to support students' spatial intelligence. This research uses Research and Development (R&D) approach by utilizing the Rowntree development model which includes planning, development and evaluation stages. The software used for development includes: Blender 3D 4.0 and Unity Hub 2022, which is used to create a virtual reality environment, displaying a combination of technological advances in education. The evaluation process for PHYVAR media and solar energy materials is carried out with validation by experts, which include material experts and media experts. Apart from that, input and assessment of media suitability were taken from the responses of 35 Class X students from a high school in Pandeglang. Validation results from both experts and students show a high level of agreement, meeting the criteria for the